Disaster Planning Tips for Caregivers of the Elderly and People with Disabilities: FCS9216/FY751, 8/2005 - Wilken, Carolyn S. (EDIS, 2005)
The purpose of this publication is to recommend specific strategies for you as the caregiver so you will be prepared for any natural disaster that may come your way. This document is FCS9216, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date August 2005. FCS9216/FY751: Disaster Planning Tips for Caregivers of the Elderly and People with Disabilities (ufl.edu)